Lewis Acid–Base Interactions between Polysulfides and Boehmite Enables Stable Room‐Temperature Sodium–Sulfur Batteries. (11th September 2020) - Ghosh, Arnab; Kumar, Ajit; Das, Tisita; Ghosh, Arpita; Chakraborty, Sudip; Kar, Mega; MacFarlane, Douglas R.; Mitra, Sagar
Abstract: Room‐temperature sodium–sulfur (RT Na–S) batteries are among the ideal candidates for grid‐scale energy storage due to their high theoretical energy density. However, rapid dissolution of polysulfides along with extremely slow redox kinetics lead to a low practical cell capacity and inferior cycling stability, inhibiting their practical applications. Herein, an innovative design strategy is introduced for a chemical and structural synergistic immobilization of sodium‐polysulfides in the cathode structure. An aluminum oxyhydroxide (AlOOH) nanosheets decorated sulfur/carbon black nanocomposite (S@CB@AlOOH) is used as an efficient cathode material for stable RT Na–S batteries. The cathode material exhibits extremely stable cycling performance, delivering an initial specific capacity of 392 mA h g –1 and retains 378 mA h g –1 after 500 cycles at 1C. The excellent performance is attributed to the synergistic effect of the structural encapsulation as well as chemical immobilization of polysulfides, significantly suppressing their gradual dissolution into liquid electrolyte. Density functional theory (DFT) calculations reveal that through favorable Lewis acid–base interactions, AlOOH catalyzes the redox conversion of the higher‐order polysulfides (Na2 S n, 6 ≤ n ≤ 8) to the lower‐order polysulfides (Na2 S x, 1 ≤ x ≤ 2). The importance of Lewis acid–base catalysis to enhance the overall performance of these batteries is demonstrated. Abstract : An ultrathin aluminum oxyhydroxide (AlOOH) nanosheets decorated sulfur/carbon black nanocomposite is used as a cathode material for room‐temperature sodium–sulfur (RT Na–S) batteries. The AlOOH nanosheets catalyze the redox conversion of sulfur to lower‐order polysulfides through Lewis acid–base interactions with intermediate polysulfides. The synergistic effect of chemical and physical encapsulation of the active material within the cathode helps to enhance the longevity of the RT Na–S batteries.